Physical therapy for patients with posttraumatic elbow contractures - Borys Pustovoit; Sviatoslava Pashkevych; Оlha Beziazychna; Tetiana Parfaniuk (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to develop and explain a modern program of physical therapy for people with posttraumatic elbow contractures during the late post-operative period using rating scales for the separate categories of International Classification of Functioning, Disability and Health (ICF) to assess the effectiveness of rehabilitation. Material and methods: the study involved 17 patients aged 28 to 50 years. The control group (CG) - 9 people (4 women, 5 men) and main group (MG) - 8 people (3 women, 5 men) were selected. The program of physical therapy in MG patients included ultrasound therapy with immediate follow-up mobilization techniques for the elbow joint in addition to conventional means. Goniometry, manual muscle testing, questionnaires Quick Disability of the Arm, Shoulder and Hand Outcome Measure (QuickDASH), Patient-rated elbow evaluation (PREE), were defined as rating scales according to literature review. Results: only 8 categories were identified, they were most significant for patients, and the corresponding ratings of the categories were established. After MG patients rehabilitation assessments of category b710 Functions of joint mobility according to the results of goniometry improved from 2.8 ± 0.2 to 1.9 ± 0.2 c.u., p <0.001, for patients of CG - from 2.9 ± 0.2 to 2.4 ± 0.6 c.u., p <0.05, with a significant difference between the comparison groups, p <0.05. Also, assessments of category d445 The using of the hand and arm according to the PREE function scale for patients of MG had positive changes: from 3.5 ± 0.5 to 2.4 ± 0.5 c.u., compared with CG - from 3.5 ± 0,5 to 3.0 ± 0.2 c.u., p <0.05, p <0.001, with a significant difference between MG and CG, p <0.05. The average duration of the late postoperative period of the MG was 21.62 ± 2.28 days, of the CG - 27.11 ± 2 , 52 days with the difference between groups, p <0.05. Conclusions: the most significant categories of IFC for the elbow contracture, their rating scales have been identified. Based on the significant differences of two IFC categories assessments (b710 Joint mobility functions, d445 Use of hand and arm, p <0.05) and reducing the duration of the rehabilitation period (p <0.05), the benefits of developed physical therapy program were proved by.